Foreign Direct Investment and Economic Growth in Nigeria from 1991 to 2021 - Adekoya, Oluwatoyosi; Adeyanju, Micheal (Acta Universitatis Danubius. Œconomica, 2025)
This research investigates the impact of Foreign Direct Investment (FDI) in developing economies growth, with a specific emphasis on Nigeria. The rate to which FDI affects the Gross Domestic Product (GDP) of Nigeria is evaluated. Utilizing the VECM (Vector Error Correction Model), the study examines both the short and long-term relationship of the dependent variable and key macroeconomic factors such as unemployment, interest rate, gross domestic investment (independent variables) amongst others. Additionally, test for normality and stability inclusive of residual autocorrelation test were performed adopting the Jarque-Bera and Lagrange Multiplier. Increase in the awareness of numerous opportunities of investment and stock market activity to enhance the capital market that will bring about a reduction in the petroleum industry reliance were recommended by the paper.